Durabilidade de Cimentos-cola utilizados na Colagem de Revestimentos Cerâmicos em Fachadas - Ana Margarida Vaz Duarte Oliveira e Sá (2005)
The use of ceramic on external wall tiling systems bedded in mortar or in cement-based adhesives, as long tradition in Portugal. However, in the last few years many pathologies, such as adhesion failure of ceramic wall tiles, appear. One of the fundamental cause is the inadequate selection of the cementitious adhesives. The performance of the adhesive is usually evaluated in the initial period. The knowledge of adhesives' characteristics at the initial moment is essential for its classification and marking. However, it does not inform us of the performance during its working life. Objective methods which are able to evaluate the building materials and components' performance through its service life are lacking. This study's main goal is to evaluate the durability of the cementitious adhesives in relation to its decreasing performance towards the tensile adhesion strength and discuss criterion of long-term selection of the most adequate adhesive to apply on external ceramic wall tilling systems. At Faculdade de Engenharia da Universidade do Porto's (FEUP) Building Physics Laboratory - LFC, about 40 samples were submitted to more than hundred accelerated aging cycles. A model to predict cementitious adhesives' service life was established through the correlation between artificial accelerated aging tests and natural aging tests. Keywords: Durability, Cementitious adhesives, Ceramic tile coating, Façades, Artificial accelerated aging tests, Natural aging tests.